2003
DOI: 10.1007/s11912-003-0110-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and diet in the development of gastrointestinal cancer

Abstract: Diet plays a role in the prevention and development of gastrointestinal cancers. The majority of available research consists of case-control studies, but the number of clinical trials is growing. The dietary recommendations to reduce gastrointestinal cancer risk include lowering total energy, fat, and saturated fat intake; avoidance of grilled and smoked foods; avoidance of alcohol; and increasing intake of fruits, vegetables, and fiber. Studies of esophageal cancer support these dietary approaches, with the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 100 publications
0
15
2
1
Order By: Relevance
“…Studies have reported that increased green tea intake may reduce risk of cancer, including gastric cancer (Thomson et al 2003); our results, however, did not show a decrease in risk of gastric cancer for subjects who consumed tea. In addition, the differences between cardiac gastric cancer and noncardiac gastric cancer were not associated with risk of gastric cancer, which does not support the possibility of different genetic susceptibility to gastric cancer at different subsites of stomach (Crew and Neugut 2004).…”
Section: Discussioncontrasting
confidence: 99%
“…Studies have reported that increased green tea intake may reduce risk of cancer, including gastric cancer (Thomson et al 2003); our results, however, did not show a decrease in risk of gastric cancer for subjects who consumed tea. In addition, the differences between cardiac gastric cancer and noncardiac gastric cancer were not associated with risk of gastric cancer, which does not support the possibility of different genetic susceptibility to gastric cancer at different subsites of stomach (Crew and Neugut 2004).…”
Section: Discussioncontrasting
confidence: 99%
“…Replacing salt/smoke with refrigeration as the primary means of food preservation and an increased intake of fresh fruits and vegetables has universally been associated with a fall in the incidence of gastric cancer among high risk populations without a change in the prevalence or virulence of H. pylori infections. [11][12][13][14] Should H. pylori be eradicated? H. pylori is a significant human pathogen responsible for considerable morbidity and mortality and is the major cause of gastric cancer.…”
Section: Outcome Of H Pylori Infectionsmentioning
confidence: 99%
“…Por outro lado, não há nenhuma evidência que suporte o papel de dieta rica em fibras ou pobre em gordura na redução dos adenomas dos cólons. 28 Se os alimentos, de um modo geral, pouco interferem com a carcinogênese cólica, a aspirina e outros antiinflamatórios não esteroidais podem ter ações interessantes, pelos seus efeitos inibitórios sobre as prostaglandinas 29 com a confirmação de que essas substâncias estariam associadas à diminuição do risco de crescimento de adenomas e de câncer do cólon. [30][31][32][33][34] Essas citações têm conotação apenas históricas, pois, na realidade, a aspirina não tem qualquer efeito protetor contra o câncer do intestino grosso 35,36 .…”
Section: A Prevenção Primáriaunclassified